Vehicle Collision Warning Based on Combination of the YOLO Algorithm and the Kalman Filter in the Driving Assistance System - Guihua Miao; Weihe Wang; Jinjun Tang; Fang Li; Yunyi Liang (Journal of Advanced Transportation, 2025)
Vehicle forward collision warning based on machine vision can help to reduce the incidence of traffic accidents. Many researchers have studied this topic in recent years. However, most of the existing studies only focus on one stage of the process such as vehicle detection and distance measurement. It will face many issues in practical application. To solve these problems, we propose a framework for forward collision warning. This study applies the YOLO algorithm to detect the vehicle and uses the Kalman filter to track the vehicle. The monocular vision distance measuring method is used to estimate the distance and travel speed. Finally, we adopt the time to collision (TTC) to decide whether to trigger the warning process. In the speed measurement stage, we design an appropriate time interval to calculate the relative speed of the front vehicle. In the collision warning segment, a TTC threshold is set by considering not only vehicle safety guarantees but also avoiding hard barking that would make drivers uncomfortable. Furthermore, we set a warning area to filter the false warning when the car overtakes and meets. Experiments with real traffic scenes demonstrate that the performance of the proposed model is good to make accurate collision prediction and warning.